2011
DOI: 10.2341/09-364-c
|View full text |Cite
|
Sign up to set email alerts
|

Oxalic Acid Under Adhesive Restorations as a Means to Reduce Dentin Sensitivity: A Four-Month Clinical Trial

Abstract: Oxalic acid may offer a novel approach to improve the reduction of dentin postoperative sensitivity after placement of resin-bonded restorations. SUMMARYThe aim of this double-blind randomized controlled clinical trial was to evaluate the reduction of dentin sensitivity using an oxalatebased compound, placed under adhesive restorations, during a four-month period. One hundred three preoperatively sensitive teeth, on 36 patients aged 25 to 66 years (mean, 40.367), were included in the study. Group A (experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…Results from a 2011 clinical study showed a significantly higher reduction in sensitivity with application of an oxalate before bonding. 38 However, authors of a critical review of the literature 62 and a critical summary 63 concluded that oxalates have not been proven effective in treating dentin hypersensitivity. Varnish also has been evaluated in reducing post–periodontal surgery root sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from a 2011 clinical study showed a significantly higher reduction in sensitivity with application of an oxalate before bonding. 38 However, authors of a critical review of the literature 62 and a critical summary 63 concluded that oxalates have not been proven effective in treating dentin hypersensitivity. Varnish also has been evaluated in reducing post–periodontal surgery root sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Results from another study of the use of oxalic acid applied before a dentin-bonding agent (DBA) adhesive showed a significantly higher reduction in sensitivity compared with use of the DBA alone. 38 Missing from these studies were comparisons with a chemoactive dentifrice and with restoration, as well as longer-term outcomes (six months or more). The authors of the oxalic acid application study 38 noted that their results were contaminated by a strong placebo effect from a water rinse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The approaches used in the treatment and prevention of CDH are tubular occlusion and/or the blockage of nerve activity. 4,8 Studies of adequate methodologic quality have been conducted to evaluate the effectiveness of laser therapy, 9,10 oxalates, 11,12 and agents at occluding dentinal tubules. 13,14 Surgical root coverage is another form of treatment for CDH and is classified as a soft-tissue pedicle graft and free softtissue graft.…”
mentioning
confidence: 99%
“…These agents promote the occlusion of dentinal tubules and reduce the movement of fluids within the tubules, with depolarization of the nerve endings leading to reduced sensitivity. However, with the exception for self‐etching adhesives, the use of these desensitizing agents before application of the adhesive system may have an adverse effect on the bond strength with dentin (Albuquerque et al, ; De Assis et al, ; Barrientos et al, ; Camilotti, Zilly, Busato, Nassar, & Nassar, ; Ding et al, ; Sartori, Lopes, & Vieira, ; Vora et al, ; West, Seong, & Davies, ).…”
Section: Introductionmentioning
confidence: 99%